2017
DOI: 10.1016/j.pestbp.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression by sedaxane increases PSII efficiency, photosynthesis and growth and improves tolerance to drought in wheat seedlings

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk Here we used a combination of chlorophyll fluorescence, gas exchange and gene expression 21 analysis, to aid our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 75 publications
3
19
1
4
Order By: Relevance
“…Recent studies have demonstrated the influence of pyrazole-carboxamide succinate dehydrogenase inhibitors (SDHIs) on plant physiology ( Ajigboye et al, 2014 , 2016 ). These comprise a relatively new class of fungicide (since 2000), and now include various active ingredients, such as boscalid, bixafen, isopyrazam and sedaxane, which can disrupt fungal respiration causing a breakdown in energy/ATP production ( Avenot and Michailides, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the influence of pyrazole-carboxamide succinate dehydrogenase inhibitors (SDHIs) on plant physiology ( Ajigboye et al, 2014 , 2016 ). These comprise a relatively new class of fungicide (since 2000), and now include various active ingredients, such as boscalid, bixafen, isopyrazam and sedaxane, which can disrupt fungal respiration causing a breakdown in energy/ATP production ( Avenot and Michailides, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Водночас не виключено, що зміни окремих показників редокс-метаболізму під впливом седаксану зумовлені його непрямими ефектами. Як уже зазначалось, у рослин пшениці під впливом седаксану зафіксовано зміну експресії сотень генів, причетних не лише до редокс-гомеостазу, а й до процесів гормональної регуляції [7]. Такі зміни можуть істотно впливати на ріст рослин за нормальних і стресових умов.…”
Section: результати та обговоренняunclassified
“…Водночас фізіологічна активність седаксану щодо рослин, ймовірно, пов'язана не лише зі змінами активності СДГ. Встановлено зміну експресії сотень генів у листках, коренях і проростаючому насінні пшениці під впливом седаксану [7]. Зокрема показано посилення експресії гена глутатіон-S-трансферази та інших генів, причетних до метаболізму глутатіону.…”
unclassified
See 2 more Smart Citations